1969
DOI: 10.1007/bf02501243
|View full text |Cite
|
Sign up to set email alerts
|

How the liquid permeability of rocks is affected by pressure and temperature

Abstract: Laboratory determinations Of the permeabilities, porosities, and residual water saturation of rocks of oil-and gas-bearing areas are usually based on data obtained under atmospheric conditions.Investigations [1][2][3][4] have shown that the reservoir properties of deeply buried rocks differ markedly from those of the same rocks under atmospheric conditions. These differences are due to the physical conditions under which the values are determined. Owing to the natural differences between the rocks which act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Several experimental studies have demonstrated temperature effects on the absolute permeability of unconsolidated sands and consolidated sandstones (Greenberg et ale 1968, Afinogenov 1969, Weinbrandt 1972, Casse 1974, Aruna 1976, and Danesh et ale 1978. In general, the main observations derived from these studies are:…”
Section: Appendix C Temperature-induced Permeability Alterationsmentioning
confidence: 99%
“…Several experimental studies have demonstrated temperature effects on the absolute permeability of unconsolidated sands and consolidated sandstones (Greenberg et ale 1968, Afinogenov 1969, Weinbrandt 1972, Casse 1974, Aruna 1976, and Danesh et ale 1978. In general, the main observations derived from these studies are:…”
Section: Appendix C Temperature-induced Permeability Alterationsmentioning
confidence: 99%